A COFs nano / BD resin composite material and its preparation method and application
By adding COFs nanomaterials to the BMI resin system and introducing low-dielectric air medium using its nanopores, the problem that the dielectric performance of existing BMI resins cannot meet the low requirements in 5G communications is solved, and the dielectric constant and dielectric are reduced The effect of loss and improves the mechanical strength and thermal stability of the material.
Patent Information
- Application Number
- CN202410667166.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-28
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-05-28
AI Technical Summary
When existing BMI resins are used in high-frequency and high-speed copper clad plates in 5G communications, the dielectric constant and dielectric loss cannot fully meet the low requirements of the communications industry.
The COFs nanomaterial is added to the bismaleimide system, and the COFs nanopores are used to introduce a low dielectric air medium to reduce the dielectric constant and dielectric loss of the system.
Through the addition of COFs nanomaterials, the dielectric constant of BD resin is reduced, so that it can meet the low dielectric requirements in the field of high-frequency and high-speed copper clad plates, and at the same time improve the mechanical strength and thermal stability of the material.
Smart Images

Figure CN118440498B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of low dielectric composite resin materials, and in particular to a COFs nano / BD resin composite material and a preparation method and application thereof. Background Art
[0002] Among high-performance resins, bismaleimide (BMI) resin, as one of the most representative resins, has shown outstanding application potential in the fields of aviation, aerospace electronic materials and integrated circuit copper clad laminates due to its excellent heat resistance, structural designability and stable dielectric properties over a wide temperature range. It has been widely used in the manufacture of high-frequency and high-speed copper clad laminate substrates. However, with the technical development requirements of the Ministry of Industry and Information Technology to "strengthen 5G evolution, support 5G-A development, and increase 6G technology research and development efforts", lower dielectric constant and dielectric loss requirements are proposed for integrated circuit copper clad laminates. At present, in 5G communications, the dielectric constant of commercial high-frequency and high-speed copper clad laminates is required to be between 2.8-3.2, and the dielectric loss factor is less than 0.005. Due to the comprehensive properties of BMI resin itself, including dielectric properties, it cannot fully meet the ever-changing needs of the communications industry. Therefore, molecular design and composite modification of BMI resin to improve dielectric properties is one of the key research directions of integrated circuit copper clad laminates. Summary of the invention
[0003] The purpose of the present invention is to provide a novel COFs nano / BD resin composite material. By adding COFs material to the bismaleimide system, the characteristics of low dielectric air medium can be introduced by utilizing the nanopores of COFs, which is beneficial to reducing the dielectric constant and dielectric loss of the system, thereby allowing the bismaleimide resin to meet the low dielectric requirements in the field of high-frequency and high-speed copper clad laminates.
[0004] To achieve the above object, the present invention provides a method for preparing a COFs nano / BD resin composite material, comprising the following steps:
[0005] 1) mixing the COFs nanomaterial and the allyl compound uniformly under ultrasonic action, and then adding bismaleimide and mechanically stirring at 135° C. to 145° C. to obtain a prepolymer of a transparent solution, wherein the mass ratio of bismaleimide to the allyl compound is 1:0.6 to 1:1.2, and the COFs nanomaterial accounts for 0.1wt% to 0.7wt% of the total amount of the allyl compound and the bismaleimide;
[0006] The COFs nanomaterial is selected from at least one of the following structures NAM-1, NAM-2, and NAM-3:
[0007]
[0008] 2) The prepolymer of step 1) is heated and cured at 140° C. to 250° C. for 8 h to 12 h to obtain a COFs nano / BD resin composite material.
[0009] As a further preferred technical solution of the present invention, in step 1), the COFs nanomaterial is polymerized and crystallized in micelles formed by amphiphilic amino acid derivatives using tetrakis(4-aminophenyl)methane and a linker;
[0010] The linking agent is any one of 2,3,5,6-tetrafluorobenzaldehyde, 4,4'-biphenyldicarboxaldehyde, and terephthalaldehyde;
[0011] The structural formula of the amphiphilic amino acid derivative is:
[0012]
[0013] In the formula, R1 is one of H, CH3, CH(CH3)2, and C(CH3)3, and the value of n is one of 1, 3, 5, 7, 9, and 11.
[0014] Further preferably, the COFs nanomaterial is synthesized using terephthalaldehyde, tetrakis(4-aminophenyl)methane, and an amphiphilic amino acid derivative in which R1 is H and n=9.
[0015] As a further preferred technical solution of the present invention, in step 1), the bismaleimide is 4,4'-diphenylmethane bismaleimide, the allyl compound is 2,2'-diallyl bisphenol A, and preferably the mass ratio of bismaleimide to the allyl compound is 1:0.8.
[0016] As a further preferred technical solution of the present invention, in step 1), bismaleimide is added and mechanically stirred at 140° C. for 30 minutes.
[0017] As a further preferred technical solution of the present invention, in step 2), heating and curing are performed by gradually increasing the temperature to 150°C, 180°C, 200°C, 220°C, and 240°C, with each heating stage lasting 2 hours.
[0018] According to another aspect of the present invention, the present invention also provides a COFs nano / BD resin composite material, which is prepared by the above method.
[0019] According to another aspect of the present invention, the present invention also provides an application of a COFs nano / BD resin composite material as a low dielectric composite resin material on an integrated circuit copper clad laminate.
[0020] Compared with the prior art, the present invention adopts the above technical solution to achieve the following beneficial effects:
[0021] 1) The pore size of the COFs nanomaterial provided by the present invention is 0.5nm to 0.67nm. Compared with metal organic frameworks, the crystalline COFs based on covalent bonds have better structural stability and smaller pore size. The structural stability of COFs can not only reduce the possibility of structural collapse of COFs during high-temperature curing, but also provide BD resin with excellent mechanical strength and thermal stability, so that it can maintain its performance stability even in long-term use or harsh environments. Its smaller pores can reduce the material's absorption and scattering of electromagnetic waves, while improving the material's ability to screen ions or molecules. Therefore, the effect of COFs nanomaterials in improving the dielectric properties of BD resin is better than that of amino metal organic frameworks;
[0022] 2) Among the COFs nanomaterials used in the present invention, NAM-1 with a pore size of 0.55 nm has the best effect on improving the dielectric properties of bismaleimide resin. At 1 MHz, the dielectric constant of the prepared NAM-1 / BD composite resin material with a COFs ratio of 0.1 to 0.7 wt% is 2.24 to 3.22, which can meet the application in commercial high-frequency and high-speed copper-clad laminates;
[0023] 3) Compared with the traditional allyl compound / bismaleimide resin system, the COFs nanomaterial / BD composite resin material prepared by the present invention has a dielectric constant of the BD resin system reduced from 3.75 to 2.2 at 1 MHz when the addition amount of NAM-1 is 0.7 wt%, which can meet the application requirements for higher dielectric properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments.
[0025] Figure 1 The dielectric constant comparison diagram of the products of comparative example 1 and examples 1-3;
[0026] Figure 2 It is a comparison chart of the dielectric loss of the products of comparative example 1 and embodiments 1-3.
[0027] The purpose, features and advantages of the present invention will be further described with reference to the accompanying drawings in conjunction with the embodiments. DETAILED DESCRIPTION
[0028] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.
[0029] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The test reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the experimental methods, unless otherwise specified, are all conventional methods.
[0030] The amphiphilic amino acid derivatives used in the following examples were prepared by the following method:
[0031] Dissolve 3.75g of glycine and 2g of sodium hydroxide in 40mL of acetone and 60mL of ultrapure water, slowly add 13.75g of palmitoyl chloride and 30ml of 6.67mol / L sodium hydroxide aqueous solution alternately at 0℃, stir with a magnetic stirrer for 2h, and obtain a white emulsion. Then adjust the pH value of the solution to 1 with 6mol / L hydrochloric acid solution, and filter through a Buchner funnel to obtain a crude product. Wash the crude product with ultrapure water until neutral, dry the water, and then soak it in petroleum ether, filter it, and dry it at 50℃ for 24h to obtain the amphiphilic amino acid derivative C16-GlyA, grind it into powder and set it aside.
[0032] The structural formula of C16-GlyA is as follows:
[0033]
[0034] Comparative Example 1:
[0035] Preparation of BD composite resin material:
[0036] Add 2.37g of 2,2'-diallylbisphenol and 2.9625g of xylene bismaleimide into a two-necked flask and stir mechanically at 140°C for 30min to obtain a reddish-brown transparent liquid, which is the BD resin prepolymer; then pour the prepolymer into a polytetrafluoroethylene mold that has been preheated at 140°C while hot and degasify at 140°C for 30min (mold molding and degassing are used to facilitate subsequent testing of dielectric properties), then cure in a flat-plate vulcanizer according to a program of heating 150°C / 2h+180°C / 2h+200°C / 2h+220°C / 2h+240°C / 2h to obtain a BD composite resin material.
[0037] Embodiment 1:
[0038] The preparation method of the COFs nano / BD resin composite material provided in this embodiment specifically comprises the following steps:
[0039] 1. Preparation of COFs nanomaterials:
[0040] 0.9402 g C16-GlyA, 15 ml of 0.2 mol / L sodium hydroxide aqueous solution and 300 ml of ultrapure water were added to a 500 ml reagent bottle, and ultrasonicated at 50°C for 30 min until C16-GlyA was completely dissolved to obtain a colorless clear solution; then 15 ml of 0.2 mol / mL hydrochloric acid solution was added, and ultrasonicated for 3 to 5 min to obtain a white emulsion, followed by adding 0.2683 g of terephthalaldehyde and ultrasonicated for 3 to 5 min;
[0041] Then, 285 mg of tetrakis(4-aminophenyl)methane was dissolved in 15 mL of 0.2 mol / mL p-toluenesulfonic acid (PTSA) solution, and the tetrakis(4-aminophenyl)methane acid solution was added to the above system and ultrasonicated for 3-5 min to obtain a bright yellow flocculent solution.
[0042] The bright yellow flocculent solution was reacted at 50°C for two weeks, the product was washed three times with ultrapure water, and then the crude product was washed three times with tetrahydrofuran. The filter cake was taken, left at room temperature overnight, and then dried at 100°C for 12h to obtain the COFs nanomaterial NAM-1, whose nanopore size was measured to be 0.55nm.
[0043] 2. Preparation of COFs nano / BD composite materials:
[0044] According to the material dosage in Table 1, NAM-1 and 2,2'-diallyl bisphenol A were ultrasonically treated at room temperature for 30 minutes, and then dimethylbenzene bismaleimide was added and mechanically stirred at 140°C for 30 minutes to obtain a prepolymer; the prepolymer was then poured into a polytetrafluoroethylene mold that had been preheated at 140°C while hot and vacuum degassed at 140°C for 30 minutes; then, the prepolymer was cured in a flat vulcanizer according to a program of heating 150°C / 2h+180°C / 2h+200°C / 2h+220°C / 2h+240°C / 2h to obtain a NAM-1 / BD composite resin material in which the COFs nanomaterial accounted for 0.1wt% of the total amount of allyl compounds and bismaleimide.
[0045] Embodiment 2 and 3:
[0046] The COFs nano / BD composite material was prepared by a method basically the same as in Example 1, except that the amount of NAM-1 was different (as shown in Table 1), and the remaining steps were the same as in Example 1, to obtain NAM-1 / BD composite resin materials in which the COFs nano material accounted for 0.3wt% and 0.7wt% of the total amount of allyl compound and bismaleimide, respectively.
[0047] Table 1
[0048] 2,2'-Diallyl bisphenol A / g Xylene bismaleimide / g NAM-1 / g Example 1 2.37 2.9625 0.0054 Example 2 2.37 2.9625 0.0161 Example 3 2.37 2.9625 0.0376
[0049] Embodiment 4:
[0050] The preparation method of the COFs nano / BD resin composite material provided in this embodiment specifically comprises the following steps:
[0051] 1. Preparation of COFs nanomaterials:
[0052] According to the preparation method of COFs nanomaterial in Example 1, terephthalaldehyde was replaced with 0.3153 g 4,4'-biphenyldicarboxaldehyde, and the other steps remained the same to obtain COFs nanomaterial NAM-2, whose nanopore diameter was measured to be 0.67 nm.
[0053] 2. Preparation of COFs nano / BD composite materials:
[0054] 0.0376 g of NAM-2 and 2.37 g of 2,2'-diallylbisphenol A were ultrasonically treated at room temperature for 30 min, and then 2.9625 g of xylene bismaleimide was added and mechanically stirred at 140°C for 30 min to obtain a prepolymer; the prepolymer was then poured into a polytetrafluoroethylene mold that had been preheated at 140°C while hot, and vacuum degassed at 140°C for 30 min, and then cured in a flat-plate vulcanizer according to a program of 150°C / 2h+180°C / 2h+200°C / 2h+220°C / 2h+240°C / 2h to obtain a NAM-2 / BD composite resin material.
[0055] Embodiment 5:
[0056] The preparation method of the COFs nano / BD resin composite material provided in this embodiment specifically comprises the following steps:
[0057] 1. Preparation of COFs nanomaterials:
[0058] According to the preparation method of COFs nanomaterials in Example 1, terephthalaldehyde was replaced with 0.3091 g of 2,3,5,6-tetrafluorobenzaldehyde, and the other steps remained the same to obtain COFs nanomaterial NAM-3, whose nanopore diameter was measured to be 0.50 nm.
[0059] 2. Preparation of COFs nano / BD composite materials:
[0060] 0.0376 g of NAM-3 and 2.37 g of 2,2'-diallylbisphenol A were ultrasonically treated at room temperature for 30 min, and then 2.9625 g of xylene bismaleimide was added and mechanically stirred at 140°C for 30 min to obtain a prepolymer; the prepolymer was then poured into a polytetrafluoroethylene mold that had been preheated at 140°C while hot, and vacuum degassed at 140°C for 30 min, and then cured in a flat-plate vulcanizer according to a program of 150°C / 2h+180°C / 2h+200°C / 2h+220°C / 2h+240°C / 2h to obtain a NAM-3 / BD composite resin material.
[0061] Comparative Example 2:
[0062] As a comparative experiment of Example 3, the COFs nanomaterial used to prepare the COFs nano / BD resin composite material in Example 2 was replaced with the same amount of amino metal organic framework material, and the specific steps were as follows:
[0063] Under nitrogen protection, 0.272g of 2-aminoterephthalic acid was dissolved in 62mL of N,N-dimethylformamide. 0.724g of AlCl3·6H2O was added, stirred at 110℃ until dissolved and kept warm for 12h. After cooling to room temperature naturally and filtering, it was washed with ethanol and then centrifuged. Subsequently, it was activated with ethanol at 90℃ for 24h and vacuum dried to obtain the amino metal organic framework material.
[0064] 0.0376 g of amino metal organic framework and 2.37 g of 2,2'-diallyl bisphenol A were ultrasonically treated at room temperature for 30 min, and then 2.9625 g of xylene bismaleimide was added and mechanically stirred at 140°C for 30 min to obtain a prepolymer; then the prepolymer was poured into a polytetrafluoroethylene mold that had been preheated at 140°C while hot, and vacuum degassed at 140°C for 30 min, and then cured in a flat-plate vulcanizer according to a program of 150°C / 2h+180°C / 2h+200°C / 2h+220°C / 2h+240°C / 2h to obtain an amino metal organic framework / BD composite resin material.
[0065] The dielectric properties of the products obtained in the above comparative examples and embodiments were evaluated using a broadband dielectric spectrometer (CONCEPT40, Novocontrol, Germany). The test temperature was room temperature, the test frequency range was 0-1 MHz, and the test sample size was 25 mm×25 mm×1 mm. The performance data are shown in Table 2.
[0066] Table 2
[0067]
[0068]
[0069] According to the attached Figure 1 , 2 From the test results in Table 2, it can be seen that since COFs nanomaterials can introduce low-dielectric air into the system, the addition of COFs nanomaterials effectively reduces the dielectric constant of BD resin. At the same time, when the pore size of the nanopore is 0.55nm, that is, when NAM-1 is added, the dielectric constant of the BD resin system is the lowest, which is 2.24-3.22 at 1MHz. When the addition amount of NAM-1 is 0.1wt% and 0.7wt%, at 1MHz, the dielectric constants of 0.1wt% NAM-1 / BD and 0.7wt% NAM-1 / BD composite materials are reduced from 3.75 to 2.86 and 2.24, respectively, significantly reducing the dielectric constant of the BD resin system. However, when the addition amount of NAM-1 is 0.3wt%, the dielectric constant of the 0.3wt% NAM-1 / BD composite material increases to 3.22. After many experiments, it was found that as the amount of NAM-1 added was between 0.1-0.7wt%, the dielectric properties of the NAM-1 / BD composite material showed a wave-like trend of first decreasing, then increasing, and then decreasing again, with the 0.7wt% NAM-1 / BD composite material having the best performance. This is because during the blending process, the suspended amino groups in the NAM-1 structure were not completely consumed by the Michael reaction or by the production of hydrogen bonds, causing the polarity of the BD resin system to increase, thereby increasing the dielectric constant of the BD resin system.
[0070] According to the test structure in Table 2, it can be seen that compared with the amino metal organic framework / BD composite resin material, the dielectric properties of the NAM-1 / BD composite material are better. In addition to introducing low dielectric air into the system, the amino groups on the COFs nanomaterials can also produce hydrogen bonds with BMI or react with the C=C on the imide ring on the BMI to increase the crosslinking density of the BD resin system and restrict the movement of the dipole. Based on the synergistic effect of these two mechanisms, the dielectric constant of the BD resin system is reduced. Through control experiments, when the addition amounts of NAM-1 and the amino metal organic framework are both 0.7wt%, at 1MHz, the dielectric constant and dielectric loss of the NAM-1 / BD composite resin material are 2.24 and 0.02291, respectively, while the dielectric constant and dielectric loss of the amino metal organic framework / BD composite resin material are 3.36 and 0.04752, respectively. From this, it can be seen that when selecting porous nanomaterials to introduce into the BD resin system, choosing new COFs nanomaterials that are connected by covalent bonds and have a more stable structure will be more conducive to improving the dielectric properties of the BD resin system.
[0071] Example 6
[0072] The COFs nanometer / BD resin composite material of the invention is applied to integrated circuit copper clad boards.
[0073] Dissolve the prepolymer in Example 3 in acetone, stir evenly with a high-speed shearing machine to obtain a glue solution for standby use. Immerse the cut electronic-grade glass fiber cloth in the glue solution, then hang it in a blast drying oven at 165-170°C, bake for 3-6 minutes, and obtain a semi-cured sheet. The obtained semi-cured sheet is stacked according to a certain stacking structure, and a copper foil is placed on the top and bottom, placed in a hot press, and hot-pressed according to the following procedure: 140°C / 1h+160°C / 1h+200°C / 2h+220°C / 4h, and naturally cooled to room temperature to obtain a 0.7wt% NAM-1 / BD resin-based copper clad laminate.
[0074] Although specific embodiments of the present invention are described above, those skilled in the art should understand that these are merely examples and that various changes or modifications may be made to the embodiments without departing from the principles and essence of the present invention. The scope of protection of the present invention is limited only by the appended claims.
Claims
1. A method for preparing a COFs nano / BD resin composite material, characterized in that: The following steps are involved: 1) mixing the COFs nanomaterial and the allyl compound uniformly under ultrasonic action, and then adding bismaleimide and mechanically stirring at 135° C. to 145° C. to obtain a prepolymer of a transparent solution, wherein the mass ratio of bismaleimide to the allyl compound is 1:0.6 to 1:1.2, and the COFs nanomaterial accounts for 0.1wt% to 0.7wt% of the total amount of the allyl compound and the bismaleimide; The COFs nanomaterial is selected from at least one of the following structures NAM-1, NAM-2, and NAM-3: 2) The prepolymer of step 1) is heated and cured at 140° C. to 250° C. to obtain a COFs nano / BD resin composite material.
2. The method for preparing the COFs nano / BD resin composite material according to claim 1, characterized in that: In step 1), the COFs nanomaterial is polymerized and crystallized in micelles formed by amphiphilic amino acid derivatives using tetrakis(4-aminophenyl)methane and a linker; The linking agent is any one of 2,3,5,6-tetrafluorobenzaldehyde, 4,4'-biphenyldicarboxaldehyde, and terephthalaldehyde; The structural formula of the amphiphilic amino acid derivative is: In the formula, R1 is one of H, CH3, CH(CH3)2, and C(CH3)3, and the value of n is one of 1, 3, 5, 7, 9, and 11.
3. The method for preparing the COFs nano / BD resin composite material according to claim 1, characterized in that: In step 1), the bismaleimide is 4,4'-diphenylmethane bismaleimide, and the allyl compound is 2,2'-diallylbisphenol A.
4. The method for preparing the COFs nano / BD resin composite material according to claim 1, characterized in that: In step 1), bismaleimide is added and mechanically stirred at 140° C. for 30 minutes.
5. The method for preparing the COFs nano / BD resin composite material according to claim 1, characterized in that: In step 2), the heating and curing time is 8h to 12h.
6. The method for preparing the COFs nano / BD resin composite material according to claim 5, characterized in that: In step 2), the heating and curing conditions are: gradually increasing the temperature to 150°C, 180°C, 200°C, 220°C, and 240°C, and the time for each heating stage is 2 hours.
7. A COFs nano / BD resin composite material, characterized in that: The method is prepared by any one of claims 1 to 6.
8. Use of the COFs nano / BD resin composite material according to claim 7 as a low dielectric composite resin material on an integrated circuit copper clad laminate.
Citation Information
Patent Citations
Mesogenic polycyanates and thermosets thereof
CA2021280A1
Fluorine-containing low-dielectric-loss bismaleimide resin, and preparation method and application thereof
CN104479130A